Abdulkader Saleh Mohammad (ed.): The Customary Law of the Akele Guzai Muslims [the Saho] (Aethiopica, 2010)
Review
Keywords: Islamic Law; Akele Guzai Muslims; Saho; Eritrea; Religion; History; Law; Tradition